Effect Of Gamma Irradiation on Yield and Quality of Guar (Cy A Mopsis Tetragonoloba ) L. Taub. - Chaudhary, M S; Ram, Het; Hooda, R S; Dhindsa, Kuldip Singh (Annals of Arid Zone, 2016)
The seeds of guar (Cymopsis tetragonoloba L. Taub.) were irradiated with 2,5, 10, 15 and 20 Kr doses of gamma rays and the X2 population was raised at the Research Farm of Haryana Agricultural University Hissar. Investigations were made to study the effect of irradiation on grain Yield and its protein and gum contents. Yield per plant has been found to increase with increasing doses of gamma rays. Similar trend has been observed for protein content of the grains. The gum. content was also higher in all the gamma ray treatments as compared to control.